Sistem Informasi Penjualan Gitar Online - Albab, Pradhika Ulil; Darussalam, Ucuk; Winarsih, Winarsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Buying and selling guitars is already popular among the general public, but guitar sales are still a lot by visiting music stores. This sales system is still a habit of people. With that, do a solution to solve the problem. The solution given is to create an e-commerce web application. By using this application is expected to simplify the sales system, data search, making it easier to create reports. This system is also equipped with item selection, so it can assist in guitar selection. Through the tests carried out, it is proven that the e-commerce web application can be used to record information about buying and selling transactions, stockpiling of goods, conducting broader promotions and marketing as well as making order transaction reports and inventory reports. The Waterfall System Development Method is used as a stage of making an application and UML (Unified Modeling Language) is used as a modeling design for the Guitar Online Sales Information System program. From the discussion and implementation of the system that has been carried out, several conclusions can be drawn, including as follows; This application can simplify the sales system at a guitar shop by providing shopping cart, search features and is equipped with a payment confirmation process as well as making it easier for the admin to record transaction reports.